Sleeping position, oxygenation and lung function in prematurely born infants studied post term. Issue 2 (24th February 2009) - Saiki, T; Rao, H; Landolfo, F; Smith, A P R; Hannam, S; Rafferty, G F; Greenough, A
Abstract : Objective: To determine the effect of sleeping position on the lung function of prematurely born infants when post term, whether any effect was similar to that before discharge from the neonatal unit, and if it differed according to bronchopulmonary (BPD) status. Design: Prospective study. Setting: Tertiary neonatal unit. Patients: Twenty infants, median gestational age 30 weeks (range 25–32); 10 had BPD. Interventions: Before neonatal unit discharge (median age 36 weeks postmenstrual age (PMA)) and when post term, infants were studied prone and supine, each position maintained for 3 h. Main outcome measures: Oxygen saturation was monitored continuously and, at the end of each 3 h period, functional residual capacity (FRC) and compliance (CRS) and resistance (RRS) of the respiratory system were measured. Results: At a median of 36 weeks PMA and 6 weeks later (post term), respectively, oxygen saturation (98% vs 96%, p = 0.001; 98% vs 97%, p = 0.011), FRC (26 vs 24 ml/kg, p<0.0001; 35 vs 31 ml/kg, p = 0.001) and CRS (3.0 vs 2.4 ml/cm H2 O, p = 0.034; 3.7 vs 2.5 ml/cm H2 O, p = 0.015) were higher in the prone than the supine position. In the prone position, both BPD and non-BPD infants had significantly greater FRCs on both occasions and oxygen saturation at 36 weeks PMA, but oxygen saturation was significantly better post term only in non-BPD infants. Twelve infants had superior oxygen saturation and 17 superior FRCs in the prone compared with the supine position at both 36 weeks PMA and post term. Conclusions: These results suggest that lung function impairment does not explain why prematurely born infants are at increased risk of sudden infant death syndrome in the prone compared with the supine position.